Optical emission spectroscopy as a method to improve the process automation of electric arc furnaces and ladle furnaces. Issue 2 (2022) - Pauna, H.; Aula, M.; Willms, T.; Echterhof, T.; Huttula, M.; Fabritius, T.
Abstract: The steel industry is on its way towards more environmentally friendly steelmaking. To achieve the ambitious goals of significant CO2 emissions reduction, new processes, practices, sources of on-line data, and digitalization together with automation will be required. To address these issues, this paper discusses optical emission spectroscopy (OES) as an on-line data acquisition method for industrial electric arc furnaces and ladle furnaces. The current state of the OES as a measurement method in the steel industry together with prospects of new applications are presented with examples based on the authors' prior research.